STRUCTURAL TYPES OF ANALYTICAL TERMS IN FORENSIC INVESTIGATION - Evgeniya V. Kovkina (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is devoted to the analysis of the structure of the terms of forensic examination. This reflects the concept of the field of forensic expertise and at the present stage requires careful regulation and standardization, since it is at the stage of its formation. In the exploration the basic structural types of analytical terms are determined taking into account the features of their grammatical structure and the number of components. Analytical models of syntactic creation of terms of forensic examination are considered. The component part of the vocabulary of forensic examination includes general scientific terms, forensic terms, terms of the related sciences (legal, legal, judicial, etc.), as well as the terms of the forensic expert examination, which are divided into groups, relevant to certain types of examinations. The specified branching of thematic blocks is reflected in the considerable quantitative superiority of analytical terminological compounds in comparison with synthetic terms. The largest quantitative characteristic is the type of two-component analytical terms. Models of such term combinations are grammatically composed predominantly of adjectives and nouns or nouns and nouns. The second type by the quantitative composition of the terms of forensic examination is the analytical three-component type of analytic terms representing the concept of almost every term group of forensic examination. Separate models among the multi-component type of terms that consist of five or more components that would have a quantitative advantage among others is not possible, since the addition of each unit also diversifies the model itself. It has been found out that the diversity of multi-component analytical terms is determined not only by the development of the conceptual apparatus of forensic vocabulary and the formation of generic relationships, but also by the need to capture the detailed characteristics of the objects, actions and attributes marked. Consequently, the term is called precisely, the smallest characteristics of it are taken into account. In expert practice, multi-component terms are used to emphasize or contrast the characteristic features of the objects under study. The feature of multi-component terms is that the meaning of the term with the addition of a new component is narrowed, specifies that contributes to the impossibility of polysemy. In the theory and practice of forensic examination, analytical terms are closer to stable expressions that can be reproduced with preservation of their semantics, despite changes in the context of the contextual environment.